Liquidity, Solvency, and Profitability Ratio Analysis as a Financial Performance Measurement Tool at PT Telkom Indonesia (Persero) Tbk for the Period 2020-2022 (Case Study of Companies Listed on the Indonesia Stock Exchange) - Indah, Sri; Lestari, Elly; Sasono, Agus Dwi; Indrihastuti, Poppy (Privietlab, 2024)
This study aims to assess the financial performance of the company using liquidity ratios, solvency ratios, and profitability ratios at PT. Telkom Indonesia (Persero) Tbk for the period 2020-2022. The type of research used in this study is descriptive quantitative research by analyzing the financial statements of PT. Telkom Indonesia (Persero) Tbk for the period 2020-2022. The data source used is secondary data, which includes annual financial statements such as income statements and balance sheets. The results of the study show that the financial performance of PT. Telkom Indonesia is as follows: (1) The calculation using the liquidity ratio with the Current Ratio formula for the last three years indicates that the company is in good con- dition, (2) The solvency ratio calculations for the last three years indicate that the company is in good condition, (3) The profitability ratio (Return on Equity) calcu- lations show that the company’s financial performance has been in poor condition over the last three years.